Analysis of Flood Disaster Mitigation in West Sumatra - Hidayat, Muhammad; Syah, Nurhasan; Erianjoni, Erianjoni (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Watershed development based on sustainable development requires open management that ensures the continuity of the coordination process between related institutions. This development is characterized by cross-sectoral and multidisciplinary. This research problem answers about 1) What is the cause of flooding in West Sumatra?; 2) What are the alternative mitigations for the flood disaster management?; 3) What are the impacts of the flood?; and 4) What are the strategic steps that can be taken?. The research study uses the library method, which is based on data obtained from the Agency of Regional Disaster Management (BPBD) West Sumatra Province in 2019. The results of this study indicate that the principles of disaster mitigation in West Sumatra have not been fully implemented, such as before a disaster, during a disaster, and after a disaster.